Generalization of the H.A. Schwarz Theorem on Stability of Minimal Surfaces - Aminov, Yuriy; Witkowska, Joanna (Журнал математичної фізики, аналізу, геометрії, 2007)
We proved two theorems on stability of minimal submanifolds in a Riemannian space, which can be included in a regular family of minimal submanifolds. Mathematics Subject Classification: 53A10, 53A07, 53C42.